2022
DOI: 10.2478/bsrj-2022-0013
|View full text |Cite
|
Sign up to set email alerts
|

Landscape of e-Learning during Covid-19: Case Study of Economic Disciplines in Croatia

Abstract: Background: The Covid-19 pandemic has changed the digitalisation level of education. Many institutions had some knowledge and practical background in delivering lectures online. Some countries apply a top-down digitalisation approach driven by policy or strategy and externally impacted by the government. Some other countries rather initiate digitalisation internally by teachers and universities. Objectives: The main goal is to investigate the digitalisation level of the higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…The pandemic encouraged the implementation of various techniques to prevent interruption in education, including flexible online learning and e-assessment. According to studies by Saikat et al (2021), Alturki and Aldraiweesh (2022), Almaiah et al (2022), andSever Mališ et al (2022), the pandemic has highlighted the potential of mobile learning. Educational systems across the globe are investigating and integrating its novel functionalities.…”
Section: Introductionmentioning
confidence: 99%
“…The pandemic encouraged the implementation of various techniques to prevent interruption in education, including flexible online learning and e-assessment. According to studies by Saikat et al (2021), Alturki and Aldraiweesh (2022), Almaiah et al (2022), andSever Mališ et al (2022), the pandemic has highlighted the potential of mobile learning. Educational systems across the globe are investigating and integrating its novel functionalities.…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic has underscored the importance of flexible and intelligent educational systems. Moreover, the pandemic has also demonstrated that mobile learning has immense potential, and education systems worldwide are increasingly exploring, promoting, and embracing its new features [3,[8][9][10]. This trend could indicate the sustainability of m-learning as an educational system.…”
Section: Introductionmentioning
confidence: 99%
“…A theoretical and empirical cross-country study involving Poland, Croatia, and Serbia [10,15,16] examined the advantages and disadvantages of e-learning during and after the COVID-19 period from the perspective of students and teachers. The study concluded that while there are disadvantages, students believe that the benefits of e-learning outweigh them.…”
Section: Introductionmentioning
confidence: 99%